1994
DOI: 10.1002/jor.1100120415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immobilization on achilles tendon healing in a rat model

Abstract: The aim of this study was to evaluate the effects of immobilization and mobilization on the functional and biomechanical recovery of injured Achilles tendons. Male Sprague-Dawley rats were allocated randomly into four groups: (a) sham operation, (b) division only (surgical transection of the Achilles tendon without immobilization), (c) "dummy" external fixation (division of the Achilles tendon and application of Kirschner wires), and (d) rigid external fixation (division of the Achilles tendon and immobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 25 publications
5
70
0
3
Order By: Relevance
“…As long as the muscle is relaxed and pliable, traction forces in the tendon callus should be low. Earlier models have used immobilization (Murrell et al 1994, Ishida et al 1996, Iwuagwu and McGrouther 1998, Yamamoto et al 1999, Palmes et al 2002, Matsumoto et al 2003. In animals, it is unclear to what extent immobilization really leads to unloading.…”
Section: Discussionmentioning
confidence: 99%
“…As long as the muscle is relaxed and pliable, traction forces in the tendon callus should be low. Earlier models have used immobilization (Murrell et al 1994, Ishida et al 1996, Iwuagwu and McGrouther 1998, Yamamoto et al 1999, Palmes et al 2002, Matsumoto et al 2003. In animals, it is unclear to what extent immobilization really leads to unloading.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate tendon mobilization accelerates the healing of an injured tendon, and immobilization prevents healing (Woo et al 1981, Gelberman et al 1982, Murrell et al 1994. The reasons for these effects may be as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was signifi cant for the fi rst weeks, but after 3 weeks the control group had caught up, which suggests that Achilles tendon ruptures should be carefully loaded during the early, rather than later, stages of healing. Murrell (Murrell et al 1994) showed that immobilization by external fi xation in a model of Achilles tendon ruptures in rats had a strong negative effect on the functional and mechanical recovery of the tendon. Immobilization of the leg after tendon transsection in rats was also studied by Rantanen (Rantanen et al 1999).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The rat tendon model was adopted and further developed from the rat Achilles tendon model described by Murrell et al (1994). The Achilles tendon complex was dissected free from other tissues ( Figure 5).…”
Section: Rat Tendon Model (Papers 1-4 6)mentioning
confidence: 99%
See 1 more Smart Citation